Bioactive Hydroxyapatite Aerogels with Piezoelectric Particles - Tavares, Catarina (2024)
Publisher Copyright: © 2024 by the authors. This work was financed by national funds from FCT—Fundação para a Ciência e a Tecnologia, I.P., in the scope of the projects LA/P/0037/202 of the Associate Laboratory Institute of Nanostructures, Nanomodelling and Nanofabrication—i3